Stories of Individual Urban Modernization in the Occupational Narratives of the Post-War Vilnius Inhabitants - Lukošienė, Mykolė (Tautosakos darbai, 2019)
After the WWII, the new inhabitants arrived to Vilnius for various reasons: some tried to escape collectivization, others planned to use the newly opened possibilities to study or work in the modern city. There were also people that had returned to Lithuania from deportation, but were banned from settling in their native communities and therefore chose Vilnius as a place to start the new phase of their lives. This article focuses on the motives related to occupation and work in the life stories of the post-war Vilnius inhabitants that settled in this city in the course of the two post-war decades. These narratives have been recorded in 2017–2019 in the course of implementing the research project “Plots of Individual Modernization in the Autobiographic Narratives of the First Generation Urban Inhabitants (Post-War Period in Vilnius)”.The modern city represented either an attractive or the only possible place for creating a new life. The increasing professional specialization is reflected in numerous stories and reveals important sides of the narrators’ identities. The article attempts to elucidate how occupational motives in the autobiographical narratives reveal the individual contributions to the formation of the modern urban culture. These motives are investigated employing the method of narrative data analysis: by establishing the most important story-lines and by associating and comparing thematically similar narratives of different people regarding their working experiences and inspirations. The occupational narrative in the life stories was regarded as an important segment of the modern urban identity. The analysis was based essentially on the notions of the modern city presented in the works by George Simmel (1950) and Michael de Certeau (1984). In all the cases it revealed modern, although rather diverse attitudes of the narrators towards their profession. These could include adapting to the newly established urban culture and making professional choices (which mostly depended on the Soviet system of studies) that were possible only in the modern urban environment. In some cases the autobiographical narratives reveal considerable anonymity partially granted by the modern Soviet city and lack of the close emotional ties, which paradoxically became a recourse for people trying to hide or escape the repressions of the Soviet political regime.
Keywords: occupational narratives; modernity; post-war Vilnius; urban anthropology